Spectrum of Malignant Skin Lesion in Patients attending Nepalgunj Medical College and Teaching Hospital - Rana, Reena; Ghimire, G P; Gupta, S; Singh, M; Jha, KK; kafle, SU (Birat Journal of Health Sciences, 2017)
IntroductionClinical diagnosis of dermatological manifestation of neoplastic skin lesion can pose a diagnostic difficulty at times. Histopathological diagnosis is mandatory for accurate characterization of disease entity for proper and timely management of cases.ObjectiveThe aim of this study was to analyze malignant tumor of skin with respect to age, sex, clinical features and histopathological features and to evaluate the accuracy of clinical diagnosis with histopathological correlation.MethodologyThis is hospital based cross-sectional study conducted at Nepalgunj Medical College and Teaching Hospital, Kohalpur from February 2010 to January 2011. A total of 70 histopathological specimens of skin biopsies were studied and correlated with the clinical diagnosis. The data was entered into Microsoft  office excel and analyzed using statistical package for social sciences (SPSS 17.0).ResultsMalignant tumor of skin constituted 21.4% of total cases. In malignant tumor, most common sites were head and neck regions followed by lower limb with keratinocytic tumors being in the majority. Most of the specimens (65.7%) were obtained as excisional biopsies.  Seven cases diagnosed as benign lesions clinically, turned out to be malignant on histopathological examination. Out of 13 cases in which clinical diagnosis was of malignancy, only 8 turned out to be malignant, thus for malignant lesions, the clinical diagnosis had a sensitivity of 53.3%, specificity of 90.9% and a positive predictive value of 61.5%.ConclusionsSquamous cell carcinoma was the most common malignant tumor in this study and histopathological correlation significantly modifies the overall management in dermatological disorders where clinical diagnoses are equivocal.Birat Journal of Health SciencesVol.2/No.1/Issue 2/ Jan - April 2017, Page: 156-161